The selection function of the RAVE survey - Wojno, Jennifer; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2017)
We characterize the selection function of RAdial Velocity Experiment (RAVE) using 2 Micron All Sky Survey (2MASS) as our underlying population, which we assume represents all stars that could have potentially been observed. We evaluate the completeness fraction as a function of position, magnitude and colour in two ways: first, on a field-by-field basis, and second, in equal-size areas on the sky. Then, we consider the effect of the RAVE stellar parameter pipeline on the final resulting catalogue, which in principle limits the parameter space over which our selection function is valid. Our final selection function is the product of the completeness fraction and the selection function of the pipeline. We then test if the application of the selection function introduces biases in the derived parameters. To do this, we compare a parent mock catalogue generated using galaxia with a mock-RAVE catalogue where the selection function of RAVE has been applied. We conclude that for stars brighter than I = 12, between 4000 < Teff < 8000 K and 0.5 < log g < 5.0, RAVE is kinematically and chemically unbiased with respect to expectations from galaxia.